Problematic use of ICTs in trainee teachers during COVID-19: a sex-based analysis - Cívico-Ariza, Andrea; Colomo-Magaña, Ernesto; Cívico-Ariza, Andrea; Ruiz-Palmero, Julio; Sánchez-Rivas, Enrique (My University, 2021)
The excessive use of ICTs is a growing problem among young people. The social isolation caused by COVID-19 can increase these inappropriate behaviour. This study aims at analysing the problematic use of ICTs in trainee teachers based on the gender variable before and after the COVID-19 lockdown based on the gender variable. A longitudinal panel design was carried out with pre-test and post-test measurements based on the gender variable. The sample consisted of 147 students from the Faculty of Education at the University of Malaga who were tested using a validated instrument: MULTICAGE-TIC. The results show that women used ICTs at a higher Both genders reach dependency level in all ICTs except for video games in women. The significant increase in all ICTs shows that the effects of the pandemic, such as restrictions on mobility and social interaction, have influenced such growth.risk than men before lockdown, except for video games. During lockdown, men obtain higher scores than women in all the analysed ICTs (except for mobile phones).
Keywords: Tecnología de la información; Conducta compulsiva; ICT; COVID-19; Addiction; Educational personnel training